2002
DOI: 10.1111/j.1151-2916.2002.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared, Raman, and Electron Spin Resonance Studies of Vitreous Alkaline Tungsten Phosphates and Related Glasses

Abstract: Ternary phosphates are found to vitrify within large domains of compositions inside the phase diagrams P 2 O 5 -WO 3 -A 2 O (A ‫؍‬ Li, Na). Structural approach of the highly modified glasses P 2 O 5 -A 2 MoO 4 -A 2 O (M ‫؍‬ Mo,W) was investigated using various spectroscopic techniques such as infrared, Raman, and electron spin resonance (ESR). These glasses were found to contain MO 6 octahedra, MO 4 tetrahedra, M 2 O 7 dimers, PO 4 tetrahedra, and also P 2 O 7 or metaphosphate chains, depending on the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 31 publications
(53 reference statements)
3
52
0
1
Order By: Relevance
“…Thus It can be assumed that with the addition of WO 3 up to 10 mol% a mixed ionic-electronic conduction mechanisms operation are simultaneously obtained, where formation of ion-polaron pair tend to decrease the conductivity and increase in the ΔE dc values in agreement with observed by [13]. The increase in dc electrical conductivity and decrease in ΔE dc with increasing WO 3 content beyond 10 mol% , could be attributed to that the electronic conduction becomes the predominant one ,where as the increase in W +5 concentration with increasing WO 3 content, increases the electronic conduction [10]. It has also been reported that in some glasses containing both alkali metal cations and transition metal ions, electrical transport is mainly electronic since alkali metal cations have small mobility.…”
Section: Ac and DC Conductivity Measurementssupporting
confidence: 84%
See 3 more Smart Citations
“…Thus It can be assumed that with the addition of WO 3 up to 10 mol% a mixed ionic-electronic conduction mechanisms operation are simultaneously obtained, where formation of ion-polaron pair tend to decrease the conductivity and increase in the ΔE dc values in agreement with observed by [13]. The increase in dc electrical conductivity and decrease in ΔE dc with increasing WO 3 content beyond 10 mol% , could be attributed to that the electronic conduction becomes the predominant one ,where as the increase in W +5 concentration with increasing WO 3 content, increases the electronic conduction [10]. It has also been reported that in some glasses containing both alkali metal cations and transition metal ions, electrical transport is mainly electronic since alkali metal cations have small mobility.…”
Section: Ac and DC Conductivity Measurementssupporting
confidence: 84%
“…W + 6 ions act as modifiers, weaken the glass network and ,thus create pathways suitable for migration of free ions that build up space charge. Thus, the weaker the network the much more is the space charge polarization which leads to an increase in the dielectric constants values [10,28]. This conclusion is further supported by the results that with increasing WO 3 content in alkali phosphate glasses, the degree of deformation of glass network will increase bonding defects, which in turn increase the space charge polarization causing an increase in the values of dielectric parameters [7,31].…”
Section: The Dielectric Constant ε \ and The Dielectric Loss Tan δsupporting
confidence: 66%
See 2 more Smart Citations
“…The role of WO3 that induces the well defined band at 943-931cm -1 from BTB-1 to BTB-6 glass system which is assigned to the stretching vibrations of B-O linkages in BO4 tetrahedra overlapping with the stretching vibrations of WO6 units [9]. There is no significant change in position of these bands.…”
Section: -2234mentioning
confidence: 89%